2006
DOI: 10.1542/peds.2005-0737
|View full text |Cite
|
Sign up to set email alerts
|

Risks for Low Intellectual Performance Related to Being Born Small for Gestational Age Are Modified by Gestational Age

Abstract: OBJECTIVE. We sought to study whether the association between being born small for gestational age and risk for low intellectual performance was modified by gestational age.METHODS. A population-based cohort study was conducted of 352 125 boys who were born between 28 and 43 completed weeks of gestation from 1973 to 1981 in Sweden. Risk for low intellectual performance at military conscription, estimated as odds ratios with 95% confidence intervals was measured.RESULTS. Compared with men who were born preterm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
50
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 32 publications
1
50
1
Order By: Relevance
“…Consistent with a recent Swedish study (19), we observed an interaction between birth size and gestational age on intellectual performance (Fig. 1).…”
supporting
confidence: 92%
See 2 more Smart Citations
“…Consistent with a recent Swedish study (19), we observed an interaction between birth size and gestational age on intellectual performance (Fig. 1).…”
supporting
confidence: 92%
“…The study by Bergvall et al (19) seems to provide similar results, although they do not compare term and preterm births directly. It has been suggested that the importance of birth weight on neurodevelopmental outcome is lower than that of gestational age (19). The interpretation of our finding may be that compared with term births, birth size in preterm infants is less predictive of the intellectual potential.…”
contrasting
confidence: 53%
See 1 more Smart Citation
“…Surviving small-for-GA (SGA) infants have a higher incidence of neurological impairments including mental retardation and educational and/or behavioral problems (1)(2)(3). Several authors have reported that perinatal hypoxic ischemic brain damage may contribute to an increased prevalence of motor, cognitive, and affective disabilities in children born with FGR (4 -6).…”
Section: F Etal Growth Restriction (Fgr)mentioning
confidence: 99%
“…Specifically, ethanol exposed fetuses showed significantly smaller fetal biparietal diameter and brain weight, consistent with prior MRI studies in murine 38 and rat 39-40 models demonstrating structural brain abnormalities resulting from first trimester ethanol exposure and microcephaly observed with fetal alcohol syndrome in human neonates 41 . Given that recent neuroimaging studies have revealed alterations in normal brain development in the setting of abnormal fetal growth [42][43][44][45] , it is possible that aberrant placental perfusion resulting in decreased oxygen availability contributed to the reduced fetal brain size. Interestingly, at G135, fetal and placental outcomes are less severe.…”
Section: Commentmentioning
confidence: 99%